Central venous obstruction in the thorax. Issue 6 (June 2015) - Collin, G.; Jones, R.G.; Willis, A.P.
Abstract : Central venous stenosis and occlusion can occur secondary to a spectrum of conditions ranging from aggressive malignancy to benign extrinsic anatomical compression in otherwise healthy individuals. Irrespective of aetiology, significant morbidity in the acute setting and long term can occur unless prompt accurate diagnosis and appropriate management is initiated, the radiologist being central to both. The present review will provide radiologists with a thorough illustration and explanation of the range of central venous conditions in the thorax (including deep vein thrombosis, thoracic outlet syndrome, haemodialysis, and malignancy related causes), the salient imaging findings and interventional management using case examples from the authors' practice. Highlights: We show a range of causes of central venous disease in the thorax. We provide information about different imaging and management strategies. We show several cases with successes and complications of endovascular management.